“LEGAL ASSISTANCE BY ADVOCATES OF LEGAL AID INSTITUTE PEDULI DAN HARAPAN BANGSA BATAM CASE NUMBER 566/Pid.Sus/2021/PN.Btm” - Zuraini Zuraini; Ninne Zahara Silviani (ConCEPt - Conference on Community Engagement Project, 2022)
The Legal Aid Institute is one of the legal aid providers according to Law No. 16 of 2011 concerning Legal Aid. The Peduli dan Harapan Bangsa Legal Aid Institute is one of the legal aid agencies in Batam City which engaged in the social and humanitarian issues. Legal assistance offered can be in the form of litigation and non-litigation. The case number 566/Pid.Sus/2021/PN.Btm is one of the case which assisted by Peduli dan Harapan Bangsa Legal Aid Institute. Therefore, the article aims to discuss how the legal assistance of Peduli dan Harapan Bangsa Legal Aid Institue in case number 566/Pid.Sus/2021/PN.Btm. The use of qualitative approach from primary and secondary data through interview, observation and documentation techniques is to answering the research problem. The results found were The Legal Aid Institute of Peduli dan Harapan Bangsa require several conditions to be met in order to get the assistance. Meanwhile, the case with the relevant case number has met the requirements given by and received a number of forms of legal assistance.